Tangled [videorecording (DVD)] - Greno, Nathan; Howard, Byron; Levi, Zachary, 1980-; Moore, Mandy, 1984-; Murphy, Donna; Garrett, Brad, 1960-; Perlman, Ron, 1950-; Tambor, Jeffrey, 1944- (Walt Disney Studios Home Entertainment : Distrubuted by Buena Vista Home Entertainment, 2011)
"When the kingdom's most wanted--and most charming--bandit Flynn Rider hides in a mysterious tower, the last thing he expects to find is Rapunzel, a spirited teen with an unlikely superpower: 70 feet of magical golden hair! Together, the unlikely duo set off on a fantastic journey filled with surprising heroes, laughter and suspense"--Container.